Studi Komparasi Penerapan Model Pembelajaran Problem Based Learning dan Inkuiri Terbimbing terhadap Keterampilan Proses Sains Siswa Kelas X SMA Negeri 3 Boyolali Tahun Pelajaran 2013/2014 - Muhamad Yutam Soleh; Slamet Santosa; Meti Indrowati (Universitas Sebelas Maret, 2014)
The purpose of this research are to determine the differences result in Sciences Process Skills (SPS) with using Problem Based Learning and guided inquiry of X grade students at SMA Negeri 3 Boyolali in 2013/2014 academic year. This research was quasi experiment research which used Posttest Only With Nonequivalent Control Group design by using the experimental 1 class (application of Problem Based Learning) and experimental 2 class (application of guided inquiry). The population studies are all X class students of SMA Negeri 3 Boyolali in academic year 2013/2014. Sampling technique is using cluster sampling, the classroom that is chosen are X.1 as the experiment 1 class and X.3 as the experimental 2 class. The techique of collecting data is using essay test for measuring of SPS classifying, using tool and material, hypothesizing, formulate ways of working, predicting and communicating. Non-test technique is using methods of documentation and observation methods for measuring of SPS using the tool and material, observing and experimenting. The data were analyzed by t-test assisted SPSS 16. The result of this research concluded that there are differences results between Problem Based Learning and guided inquiry toward student’s sciences process skills of X grade students at SMA Negeri 3 Boyolali. Key Words: Problem Based Learning, Guided Inquiry, Science Process Skills